Influence of Personal Factors and Personal Behaviors as a Moderator Linked to Marketing Mix (4Cs) Perception to the Credibility of an Accommodation Source through an Online Travel Agencies (OTAs) - Chaiyakhet, Netdao; Sangsuwan, Tinikan (Journal of Applied Economics and Management Strategy, 2025)
Strategic marketing planning has prompted research into the moderating effects of individual factors (gender and education) and user behavior (social influence and prior experience with Online Travel Agencies: OTAs) on the relationship between perceptions of the marketing mix (4Cs) and the perceived credibility of accommodation sources provided through OTAs. This quantitative study employed purposive sampling and utilized a closed-ended questionnaire to collect data from 393 Thai tourists in the Bangkok area who had prior experience using OTAs via websites and mobile applications. Descriptive statistics, including means and standard deviations, were used for preliminary analysis. Inferential analysis was conducted using Structural Equation Modeling (SEM) to assess the model’s goodness of fit and to perform pairwise parameter comparisons to examine differences and statistical significance in the path coefficients across the two groups. The research findings indicate that age, education, and social influence do not produce significant differences in moderating the relationship between the perception of marketing mix elements and the perceived credibility of accommodation sources on OTAs. However, prior experience with OTAs-particularly with the Agoda platform-demonstrates a positive and distinctive influence compared to experiences with other OTAs. This suggests that users with experience using Agoda exhibit greater trust in accommodation sources than those using alternative platforms. Therefore, these findings can be applied to the development of targeted marketing strategies aligned with specific customer segments.